Analysis of Working Capital Management and its Impact on Business Performance in SMEs: Working Capital Management and Its Impact on the Performance of MSMEs - Andi Jamaluddin; Andi Nurwana (Maneggio, 2025)
Working capital management is a critical aspect that determines the sustainability and performance of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze working capital management practices and their impact on MSME performance through a qualitative approach. Data were collected through in-depth interviews with business owners, observations, and analysis of simple financial documents. The study findings revealed that most MSMEs face obstacles in working capital management, particularly related to irregular cash flow, accumulating receivables, and suboptimal inventory management. Informal practices and a lack of systematic planning are the main causes of working capital inefficiency. However, the study also found that MSMEs that disciplinedly apply basic working capital management principles—such as receivables control, inventory rotation, and regular cash monitoring—demonstrated more stable business performance. These results align with various previous studies that confirm a positive relationship between working capital efficiency and increased MSME profitability. This study concludes that improving managerial capacity through financial literacy and supporting access to financing are key to optimizing MSME working capital management. The implications of this research not only provide academic contributions in understanding the challenges of working capital management at the MSME level, but also offer practical recommendations for business actors and policy makers in increasing the competitiveness of small and medium enterprises.